Diagnosis of the public water supply in the city of Maringa, PR and its relation to the concept of smart cities - Nakahashi, Roberto Takeshi; Rodrigues Júnior, Alinor; Juliani, Bruno Henrique Toná; Okawa, Cristhiane Michiko Passos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
With the development of cities in a more integrated and innovative management for urban sectors, the smart cities emerge, usually incorporating this evolution using the Information and Communication Technology (ICT), necessitating investments in technology and innovation in the public policies. In light of this context, the purpose of this paper was to carry out the diagnosis of the city of Maringa concerning innovation and the use of ICT in the potable water public supply sector. It was conducted interviews with the responsible for the concessionaire of the water supply in Maringa (SANEPAR), and also document evaluations. The results attest to the development of a project elaborated by SANEPAR in partnership with Parana Meteorologic System (SIMEPAR), with the intention of a more intelligent water supply system, that allows the prediction of possible floods in the water catchment plant by heavy rainfall. Thus, it can be concluded that there is the intention of implementing smart technologies, beginning with the protection to the catchment of the water, that can be extended to the operation of the whole water supply system of the municipality of Maringa.